Arthroscopic Biologic Shoulder Tuberoplasty Irreparable Supraspinatus Tears: The “4-Corner” Technique - Georgios Mamarelis, M.D., F.R.C.S.Ed. (Tr. & Orth.), P.G.Cert. Med. Ed.; Michele Novak, M.D.; Tong Liu; Ian K.Y. Lo, M.D., F.R.C.S.C. (Arthroscopy Techniques)
The management of massive irreparable rotator cuff tears in young patients without degenerative joint changes or patients who are unsuitable for arthroplasty remains controversial. Biologic tuberoplasty can be a valuable option for patients without pseudoparalysis with preserved glenohumeral cartilage and a good passive range of motion. This is because the acellular dermal allograft covers the tuberosity, acting as an interpositional tissue and preventing bone-to-bone contact between the tuberosity and acromion. In addition biologic tuberoplasty can be faster, less technically demanding, and can lead to accelerated recovery, making this technique attractive. This technique aims to provide a practical solution with modifications to reduce surgical duration, enhance efficiency and reproducibility, and facilitate functional recovery and pain relief.